2018
DOI: 10.1002/ece3.4084
|View full text |Cite
|
Sign up to set email alerts
|

Guano exposed: Impact of aerobic conditions on bat fecal microbiota

Abstract: Bats and their associated guano microbiota provide important terrestrial and subterranean ecosystem services and serve as a reservoir for a wide range of epizootic and zoonotic diseases. Unfortunately, large‐scale studies of bats and their guano microbiotas are limited by the time and cost of sample collection, which requires specially trained individuals to work at night to capture bats when they are most active. Indirectly surveying bat gut microbiota through guano deposits could be a more cost‐effective alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…All animals included this study displayed no apparent clinical signs of illness based on their normal behavior as well as smooth fur appearance. The sampling process, in brief, was performed by spreading an aseptic plastic cloth under bat colonies and waiting until sufficient fecal samples to be collected (normally 1-2 h) (Fofanov and Furstenau, 2018). Samples were frozen in liquid nitrogen immediately after collection.…”
Section: Sample Collection and Phylogenetic Determinationmentioning
confidence: 99%
“…All animals included this study displayed no apparent clinical signs of illness based on their normal behavior as well as smooth fur appearance. The sampling process, in brief, was performed by spreading an aseptic plastic cloth under bat colonies and waiting until sufficient fecal samples to be collected (normally 1-2 h) (Fofanov and Furstenau, 2018). Samples were frozen in liquid nitrogen immediately after collection.…”
Section: Sample Collection and Phylogenetic Determinationmentioning
confidence: 99%
“…Successful sequencing has been found to be higher for fresher feces [9, 10], and for samples collected in conditions such as cold temperatures [11, 12], dry climates with protection from precipitation [13], and low UV exposure [14]. Further, DNA response to these variables has been found to be taxon-specific (e.g., accurate genotyping after 2 months in feral horses [15], errors after 7 days in coyotes [16]) and target-specific (from bat guano: change in bacterial community composition after 1 hour [17], identification of bat species at 3 months [3]). DNA concentration can also vary by collection/preservation method [15, 18] and by the order the feces traveled through the intestines [19].…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation is the potential degradation of material collected inside the cave, especially for feces droppings, as we cannot exactly tell the time since defection for these samples (even if we tried to minimize it by collecting the freshest droppings). A recent study showed indeed that a rapid reduction in fecal microbiota diversity can be expected after 1 hr post‐defecation, especially for anaerobic bacteria (Fofanov et al, ). For our indirect urine samples, material degradation should be limited as these samples were collected rapidly (within 20 min).…”
Section: Discussionmentioning
confidence: 99%